Vibration characteristics of h-FGS plates resting on an elastic foundation under double blast loading - Ngoc-Tu Do; Pham Binh Le; Truong Son Le; Trung Thanh Tran; Quoc Hoa Pham (Alexandria Engineering Journal, 2024)
The main goal of this paper is to use the higher-order isogeometric analysis (IGA) to study the vibration behaviour of sandwich plates with an auxetic honeycomb core and two different functionally graded materials (FGM) skin layers (namely h-FGS plates) resting on an elastic foundation (EF) under double blast loading. Reddy's HSDT is used due to its simplicity and efficiency. The foundation model incorporates two parameters as springer stiffness (k1) and the shear layer stiffness (k2). The governing equation is derived from Hamilton's principle. After verifying the present approach, the effect of input parameters on the vibration characteristics of h-FGS plates is carried out in detail. The obtained results are expected to be useful for calculating and designing h-FGS plates in practice.